Fundamentals of Physics and Chemistry of the Atmosphere - Visconti, Guido (Springer International Publishing : Imprint: Springer, 2016)
This book is an introductory course to the physics and chemistry of the atmosphere and to climate dynamics. It covers the basics in thermodynamics, fluid dynamics, radiation, and chemistry and explains the most intriguing problems that currently exist in the study of the atmospheres of the Earth and planets. A particular effort is made to approach the different topics intuitively. Among the themes covered are the most recent evolution concerning the chemistry of polluted troposphere, the global warming problem, and chaos and non linear theory. The book is almost completely rewritten in comparison to the previous edition, with a more logical organization of the chapters. The fundamentals of thermodynamics, radiation, fluid dynamics and chemistry are introduced in the first six chapters including a new chapter on remote sensing. Also there is an additional chapter on Geoengineering. A significant addition to the new edition, at the end of each chapter, are the Examples where the topics introduced in the chapter are further discussed with application to classical problems or new research items. Many of these examples are accompanied by computer programs. The most important update deals with the theory of the general circulation, the methods to evaluate GCM, the detailed discussion of the urban troposphere and the chaos and non linear phenomena.